Paleoenvironmental Conditions of the Harur Formation (Early Carboniferous), Northern Iraq: Insights from Mineralogy and Elemental Geochemistry - Al-Lhaebi, Safwan F.H.; Al-Khatony, Flyah H.; Hussain, Salim H.; Al-Juboury, Ali I.; Rowe, Harry; Zanoni, Giovanni (Iraqi Journal of Science, 2024)
The early Carboniferous Harur Formation from the Ora outcrop section of northern Iraq consists of black shale, calcareous shale and carbonate. The mineralogical and geochemical investigations (major and trace elements) of the black shale and calcareous shale units have been conducted to evaluate paleoenvironmental conditions including paleoclimate, paleoredox conditions, paleoproductivity, sedimentary rate, and to evaluate their effects on organic matter accumulation. The geochemical proxies such as the Chemical Index of Alteration (CIA), A-CN-K plot, Sr/Cu ratio, and the relation between the ratio of Ga/Rb and Sr/Cu suggest moderate to intense chemical weathering under humid conditions. The Rb/K and Sr/Ba ratios indicate a freshwater environment during deposition. Multiple paleo-redox indicators such as ratios of V/(V+Ni) and Th/U) and U index indicates deposition under depleted marine oxygen conditions and consequently recording an Ocean Anoxic Event (OAE). The Th/U ratio indicates that the sedimentary rate at the lower part of the section is less than that of the upper part of the section. The terrigenous clastic input index (Ti and Al) shows that clastic input reduced from the lower to the upper section which implies that the sea level rose first lower to the upper section. Both Al and Ti have positive correlations with TOC (Total Organic Carbon) which reveal that clastic input was advantageous for OM accumulation. The high ratios of (Fe + Mn)/Ti and the presence of nacrite minerals indicate hydrothermal activity during deposition. Hence, the main control factors of OM accumulation in the black shale and calcareous shale of the Harur Formation were terrigenous clastic fluxes, in addition to paleo-redox conditions and hydrothermal activities. On contrary, paleoproductivity proxies play a relatively less significant role in OM accumulation.